Menumbuhkan Minat Belajar Bahasa Inggris Anak Usia 5-9 Tahun Melalui Pembelajaran Kosakata Berbasis Gambar - Pratiwi, Nindyah; Dwi Wahyu Pril Ranto (Sekolah Tinggi Ilmu Bisnis Kumala Nusa, 2025)
Abstract This community service was designed to build interest in learning English among children aged 5 to 9 years in Dusun Tegal Blateran, Klaten, utilizing picture-based vocabulary instruction. The implementation of the program was grounded in a learning assistance framework enlightened by the theories of the Zone of Proximal Development (ZPD) and scaffolding. The activities encompassed introducing English vocabulary through visual aids, engaging in drawing exercises, and conducting guided vocabulary practice sessions. The outcomes indicated that the children exhibited a high level of enthusiasm, willingly adhered to instructions, and demonstrated confidence in utilizing English vocabulary. The involvement and parents’ support, alongside community leaders, significantly contributed to the program's success. Overall, this activity had a positive effect on the children's interest in learning and heightened community awareness regarding early English education. Keywords: Children English learning, picture-based vocabulary, community service